Cultura é desenvolvimento:um panorama da atuação do BNDES em projetos de restauro (1997-2007) - Schneider, Simone Marafon (2008)
This study has the objective of examining the performance of the National Bank of Economic and Social Development (BNDES) in projects developed to preserve the Brazilian architectural heritage. Towards this objective, the study outlines the path chosen by BNDES over the years to support culture in Brazil, emphasizing selected projects implemented under the Rouanet Law from 1997 to 2007. The result is a historic overview that explains when - and how – culture became part of BNDES agenda and, more specifically, why, within alternatives of investment in culture, BNDES chose to value/prioritize the improvement of restoration projects in Brazil, a responsible choice for transforming BNDES, the largest bank development in Latin America, in the major sponsor of initiative focused on restoration, conservation and adaptation of the national cultural patrimony.